Global Health and the Millennium Development Goals. Issue 5 (September 2015) - Ryan, Jane Greene
<x xml:space="preserve">Abstract</x> The Millennium Development Goals (MDGs) have not been fully achieved; much more work is needed to better the lives of families around the world. The three feature articles in this special topics series on international issues in maternal child nursing provide information on some of the challenges in meeting the objectives of the MFGs affecting women and children.